Lublin climate research - Kaszewski, Bogusław M. (Acta Geographica Lodziensia, 2019)
Based on scientific literature, from the historical perspective, the state of research on Lublin’s climate since the mid-nineteenth century has been presented. The number of studies in this field until the end of World War II was small, due to the lack of a long homogeneous series of data. The progress in climate research in Lublin was marked by the data obtained from three new meteorological stations which were established in the 1940s and 1950s. Three main groups of papers were distinguished: 1st – regarding variability of individual meteorological elements and selected bioclimatic characteristics and indicators, 2nd – regarding the distinctiveness of Lublin’s climate in relation to extra-urban areas and to other cities, 3rd – regarding spatial diversity of selected elements of weather and climate in the city.